Impact of dentofacial esthetics in self-esteem. A review of the literature. (International Journal of Medical and Surgical Sciences, 2018)
At the national level, it is considered that around half of 12-year-old children have some type of malocclusion. This problem gives rise to negative functional and esthetic consequences that produce a dissatisfaction in the individual, which is related to the severity of the dental irregularities. Even so, there are differences in their recognition and evaluation, given that it is not uncommon to observe some patients with severe malocclusions who are satisfied with their dental esthetics. Physical and facial appearance play a fundamental role in interpersonal communication; therefore, malocclusion can have a negative effect on social relationships, affecting the self-image and self-esteem of individuals. The objective of this article is to describe the results reported in the literature about the impact of dentofacial esthetics on self-esteem. Evidence about the impact of malocclusions and their relationship with general self-esteem and psychosocial disorders of dentofacial esthetics is varied; there is no direct association between these three measurements in all cases. Below, we present some interesting studies and evidence. The studies reveal the association that exists between malocclusion, general self-esteem and psychosocial disorders in relation to dentofacial esthetics. The majority of studies are in adolescent populations at the national and international level. This clearly shows the lack of studies in young or university age populations, which is of interest in dentistry and public health.
Keywords: dentofacial esthetics; self-esteem; self-concept